Pradhan Mantri Fasal Bima Yojana A bonanza for farmers - Vincent, A; Manjuprakash, Manjuprakash; Kumar, M Senthil (Indian Farming, 2017)
The scheme PMFBY helps the farmers during adverse conditions asthe scheme provides financial support to them, mitigate the crop losses incurred. Besides, the scheme facilitates the farmers to contribute to the national objective of achieving sustainable farming.